SURVEY OF URINARY ALBUMIN RATE IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES - Thiện Đức, Trần; Văn Bé Hai, Nguyễn; Thị Trang, Dương; Thị Phương Dung, Nguyễn; Thuỳ Dung, Nguyễn (Journal of Health and Aging, 2025)
Albuminuria is a key marker for early kidney damage and cardiovascular risk in patients with diabetes and hypertension, even when glomerular filtration rate (GFR) is preserved. However, data on the prevalence of albuminuria in Vietnamese populations remains limited. To assess the prevalence of albuminuria and its associated clinical factors in patients with type 2 diabetes and/or hypertension. This cross-sectional study included 209 patients at Thong Nhat Hospital, Ho Chi Minh City. Clinical characteristics, blood pressure control, and laboratory data including urinary albumin-to-creatinine ratio (UACR) were collected. Albuminuria was defined as UACR ≥30 mg/g, including microalbuminuria (30–299 mg/g) and macroalbuminuria (≥300 mg/g). Logistic regression was used to identify factors associated with albuminuria. The mean age was 68.04 ± 13.94 years, and 38.8% had type 2 diabetes. Overall, 27.7% of patients had albuminuria, including 16.7% with microalbuminuria and 11.0% with macroalbuminuria. Blood pressure was controlled in 58.7% of participants. Only 42.5% of diabetic patients achieved glycemic targets. Macroalbuminuria was significantly more common in patients with uncontrolled blood pressure (18.6% vs. 5.7%, p < 0.01). No significant associations were found between albuminuria and age, sex, or ASCVD. Albuminuria is prevalent in patients with diabetes and hypertension, particularly among those with uncontrolled blood pressure. These findings support routine screening for albuminuria and early initiation of renoprotective therapy to prevent renal and cardiovascular complications in high-risk Vietnamese populations.